Preliminary data on the development of emotion vocabulary in typically developing children (5–13 years) using an experimental psycholinguistic measure - Sturrock, Alexandra; Freed, Jenny (Frontiers in Psychology, 2023)
Vocabulary of emotion is integral to emotional development (Doyle & Lindquist, 2018) and emotional intelligence is associated with improved mental health outcomes (Martins et al, 2010). Many language disordered groups experience emotional difficulties; Developmental Language Disorders (St Clair, et al, 2019), ADHD (Christiansen, et al., 2019) and autism (Cibralic et al, 2019). However, (as in the case of autism) research tends to focus on assessing recognition of emotional states (Nuske, et al., 2013), rather than exploring labelling skills. Where labelling is assessed, measures have focused on early-acquired vocabulary (happy, sad, angry) or self/parent reporting (Baron-Cohen et al, 2010). To date no objective assessment has been made of vocabulary of emotion across childhood. This study uses an experimental psycholinguistic measure, The Emotion Vocabulary: Expressive and Receptive ability measure (EVER) which includes two tasks (receptive vocabulary and word generation/expressive vocab). This measure has capacity to demonstrate vocabulary growth across age groups (Sturrock et al, 2019). 171 participants (5.0-13.11) completed The EVER Measure, alongside two closely matched standardised measures of basic language: BPVS (receptive vocabulary task) and CELF (word-association task). Assessments were completed online and en vivo (COVID testing restrictions dependent). As predicted, results indicate that children’s accuracy increased on both receptive and expressive emotion vocabulary tasks, in line with age at time of testing. EVER scores were significantly predicted by age and correlated with matched basic language scores. Secondary analysis provided preliminary findings on age of acquisition for specific emotion vocabulary items. The findings consequently demonstrate validation for the use of The EVER Measure in assessing emotional vocabulary across childhood. This study provides important preliminary data on generating and recognising emotion labels across typical child development. Critically, it extends current knowledge on emotion vocabulary acquisition into middle childhood, where linguistic ability is relatively mature. As such, findings have implications for research with potential clinical application in the assessment of older children, with either language or emotional differences or both. Findings demonstrate the need for a standardized tool, and its potential application in research and clinical practice is explored. A large-scale study offering validation and reliability of The EVER Measure is indicated.